2022
DOI: 10.1017/lap.2022.46
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Interrupted: A New Framework for Understanding Anti-Left Sentiment Among Brazil’s “Once-Rising Poor”

Abstract: How do sequences of upward and downward socioeconomic mobility influence political views among those who have “risen” or “fallen” during periods of leftist governance? While existing studies identify a range of factors, long-term mobility trajectories have been largely unexplored. The question has particular salience in contemporary Brazil, where, after a decade of extraordinary poverty reduction on the watch of the leftist Workers’ Party (PT), a subsequent period of economic and political crises intensified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In any case strong antipetismo seems to have been a minor component of support for Bolsonaro among lower-income voters (Nicolau, 2020). On the other hand, in a large survey study, Junge et al (2022), found that upwardly mobility poor Brazilians whose mobility was stalled during the economic crisis were more likely to express anti-left sentiment than those who had not experienced any mobility. This suggests that frustrated expectations and a sense that the PT favoured only the very poor, in particular welfare beneficiaries, may have played a key role in growing rejection of the Party among the “previously poor”.…”
Section: Brazil’s Rightward Turnmentioning
confidence: 96%
“…In any case strong antipetismo seems to have been a minor component of support for Bolsonaro among lower-income voters (Nicolau, 2020). On the other hand, in a large survey study, Junge et al (2022), found that upwardly mobility poor Brazilians whose mobility was stalled during the economic crisis were more likely to express anti-left sentiment than those who had not experienced any mobility. This suggests that frustrated expectations and a sense that the PT favoured only the very poor, in particular welfare beneficiaries, may have played a key role in growing rejection of the Party among the “previously poor”.…”
Section: Brazil’s Rightward Turnmentioning
confidence: 96%